Comparison of Periodontal Status in Gingival Oral Lichen Planus Patients and Healthy Subjects. (18th April 2012) - Azizi, Arash; Rezaee, Massoud
Abstract : Background and Objective . Oral lichen planus (OLP) is a common chronic mucocutaneous disease. OLP can occur in different oral sites such as gingiva. The purpose of study was to evaluate the periodontal status of OLP patients with desquamative gingivitis (DG) and compare it with that of healthy control. Methods . This study was case-control. 32 patients with gingival OLP as a case group and 32 healthy subjects as a control group were selected. The periodontal status of all subjects including plaque index (PI), bleeding on probing (BOP), and clinical attachment level (CAL) was evaluated in both groups. Finally data were analyzed by t -test. Results . The mean values of periodontal parameters were observed to be higher in case group compared with control group, and this was significant (P < 0.05 ). Conclusion . Our results showed that periodontal status is worse in gingival OLP if compared with healthy controls.